(untitled) (Advances in Knowledge Representation, 2023)
In the digital age, information is easily disseminated in communication networks. New ways of thinking, acting and experiencing are emerging all the time in the world of communication and technology. All industrial sectors are being hit by the digital transformation. New business models emerge based on a new global platform, the Internet. With Financial Institutions (FI) the situation is no different, they need to reinvent themselves, to compete with each other, and face the threats of new competitors that were born digital. In FIs, the way of offering products and services to the customer is of paramount importance for their success, and from this perspective, the emergence of highly technological financial startups (fintechs) challenge FIs. Fintechs facilitate access to financial services, and bring convenience to the customer through technological innovation. Given this scenario, the objective of this study is to analyze the relationship between information technology (IT), knowledge management and innovation in the creation of value in FIs. The research addresses topics such as Web 2.0, IT, business model, knowledge management and innovation, presenting IT as a catalyst for innovation. To analyze the impact of IT, Web 2.0, knowledge management and business model in relation to innovation, a descriptive qualitative and quantitative research will be carried out. Research data were collected through a questionnaire (e-survey), created from the theoretical framework.